Development of Learning Media Based on Android on Sterilization and Explant Planting - Arifah (Jurnal Pendidikan Biologi Undiksha, 2022)
Sterilization and explant planting practice can help utilize plant parts to regenerate quickly and can be adjusted according to current needs. Developments in the field of education must also accompany the development of science and technology. Because the material discussed emphasizes the process dimension of learning with practical and experimental guidance, it is very suitable for developing students' knowledge and skills and discovering the basic concepts of tissue culture for themselves. This study aims to find out the feasibility of learning media based on android on the topic of sterilization and explant planting in tissue culture subject matter. The study employs an ADDIE-based development study design that incorporates analysis, design, development, implementation, and evaluation. The developed media product is a learning media application in the apk. format that is compatible with Android smartphone devices. From April 2022 to September 2022, the survey was carried out. The media expert outcomes for the Learning Media Approval Test showed him accomplishing a score of 90,625 in the very worthy class. The learning media feasiility test, which was administered by experts in teaching materials, gave a score of 95.5 points, which is very worthy to use. The tissue culture lecturer's responses to the learning media received a score of 78.056, which is very good category. The student responses to the learning media were rated "very good" with 91.5 points. It has been well received by experts, a tissue culture lecturer, and biology majors who have used it as an Android-based learning media.